Dynamic Fracturing Behavior of Layered Rock with Different Inclination Angles in SHPB Tests - Jiadong Qiu; Diyuan Li; Xibing Li; Zilong Zhou (Shock and Vibration)
The fracturing behavior of layered rocks is usually influenced by bedding planes. In this paper, five groups of bedded sandstones with different bedding inclination angles θ are used to carry out impact compression tests by split Hopkinson pressure bar. A high-speed camera is used to capture the fracturing process of specimens. Based on testing results, three failure patterns are identified and classified, including (A) splitting along bedding planes; (B) sliding failure along bedding planes; (C) fracturing across bedding planes. The failure pattern (C) can be further classified into three subcategories: (C1) fracturing oblique to loading direction; (C2) fracturing parallel to loading direction; (C3) mixed fracturing across bedding planes. Meanwhile, a numerical model of layered rock and SHPB system are established by particle flow code (PFC). The numerical results show that the shear stress is the main reason for inducing the damage along bedding plane at θ = 0°~75°. Both tensile stress and shear stress on bedding planes contribute to the splitting failure along bedding planes when the inclination angle is 90°. Besides, tensile stress is the main reason that leads to the damage in rock matrixes at θ = 0°~90°.